TWORZENIE SYSTEMU LOTNISK CYWILNYCH DLA BEZPIECZEŃSTWA NARODOWEGO: LOTNISKO WARSZAWA/MODLIN W MIEJSKIM OBWODZIE WARSZAWY - KOSTRZEWA-ZORBAS Grzegorz (2013)
A former military air base of the Warsaw Pact era serves now several purposes of broadly defined national security of Poland. With EU help, regional and local self-government and the national government together converted the base into the new civil Warsaw/Modlin Airport. The article identifies twelve reasons for, and benefits from, the establishment of the second international civil airport in the Warsaw Metropolitan Area, besides the old Warsaw Chopin Airport: 1. Diversification, resilience and invulnerability of the aviation infrastructure as part of the critical infrastructure of Poland, NATO and the EU; 2. Stability of air transportation – including government and military flights – between the capital of Poland and the rest of Europe and the world; 3. A strong and resilient system of airports also for commerce and pleasure, including private business travel, tourism, mail and cargo; 4. Assured connections to the rest of Poland, Europe and the world for non-government and non-military flights, including mail and cargo ones; 5. A closer access to air transportation for the part of the region located far from the Warsaw Chopin Airport; 6. Prospects for further growth of the aviation infrastructure thanks to a large reserve of space in Modlin; 7. Economic benefits from the specialization of airports; 8. Cheaper air travel thanks to the increased presence of low-cost airlines and their competition; 9. Local and regional economic growth, development and modernization with a prospect for an “Airport City” of advanced economy in Modlin; 10. An economically beneficial conversion of no longer needed military property for civil use; 11. A better quality of life in Warsaw and the part of the Warsaw Metropolitan Area surrounding the Warsaw Chopin Airport, thanks to diversification of air traffic and associated road traffic; 12. Protection of the environment thanks to geographic diversification of air operations and to a railroad line between the two airports and Warsaw that will replace a large share of automobile traffic associated with air travel, mail and cargo. In addition, the nearby Modlin Fortress of a great architectural and historic value may attract more interest, visitors, care and investment, contributing to national security of Poland and its allies and partners through education.